2022
DOI: 10.1021/acs.analchem.2c03093
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Air Battery-Based Self-Powered Sensor with High Output Power for Ultrasensitive MicroRNA let-7a Detection in Cancer Cells

Abstract: Self-powered sensors do not require a power supply and are easy to miniaturize, which have potential for constructing wearable, portable, and real-time detection devices. However, it is challenging for the detection of low abundant targets due to the low output power density of fuel cells and much interference of complex biological environment. Herein, a new kind of photocatalytic zinc−air battery-based self-powered electrochemical sensor (ZAB-SPES) was constructed for the detection of microRNA let-7a (miRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition to the studies mentioned above, several other near-commercial miRNA biosensors have been developed. Jin et al [62] combined magnetic nanobeads with metalorganic frameworks loaded with glucose oxidase (MOFs@GOX) and constructed a novel The linear detection range of this biosensing platform is 1-200 ng/mL. In the PBS buffer, the LOD for miRNA-155 was calculated to be 17.0 ng/mL and the LOD for miRNA-21 was 9.2 ng/mL through linear fitting.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the studies mentioned above, several other near-commercial miRNA biosensors have been developed. Jin et al [62] combined magnetic nanobeads with metalorganic frameworks loaded with glucose oxidase (MOFs@GOX) and constructed a novel The linear detection range of this biosensing platform is 1-200 ng/mL. In the PBS buffer, the LOD for miRNA-155 was calculated to be 17.0 ng/mL and the LOD for miRNA-21 was 9.2 ng/mL through linear fitting.…”
Section: Other Methodsmentioning
confidence: 99%
“…In addition to the studies mentioned above, several other near-commercial miRNA biosensors have been developed. Jin et al [62] combined magnetic nanobeads with metalorganic frameworks loaded with glucose oxidase (MOFs@GOX) and constructed a novel self-powered electrochemical sensor based on a photocatalytic zinc-air battery (ZAB-SPES) for the detection of miRNA let-7a. ZAB-SPES has a high-power density of 22.8 µW/cm 2 , which is 2-3 times higher than that of commonly used photofuel cells.…”
Section: Other Methodsmentioning
confidence: 99%
“…By replacing the traditional platinum plate electrode, the application of p-type photomaterials effectively expands the difference between the Fermi energy levels between the electrodes, thus generating greater self-bias to drive the PFCs . In addition, owing to the detection signal being attributed to the photocathode, it shows great significance to construct a photocathode with excellent environmental friendliness and ideal stability. , Dual-photoelectrode fuel cell (DPFC) based SPSs have been proposed, through integrating n-type and p-type semiconductors as a photoanode and photocathode, respectively. , …”
Section: Introductionmentioning
confidence: 99%
“…Numerous pathological studies have shown that the abnormal expression of miRNA let-7a in tumor cells and serum is correlated to many cancers, such as hepatocellular carcinoma (HCC), breast cancer, and pancreatic cancer, making miRNA let-7a one of crucial cancer biomarkers. At present, a variety of methods have been developed to detect miRNA let-7a, such as electrochemiluminescence, , fluorescence assays, and electrochemical methods. , Compared to the other methods, the electrochemical biosensing technology has the advantages of simpleness, low cost, and high sensitivity, which are more conducive to the establishment of practical analytical devices.…”
Section: Introductionmentioning
confidence: 99%
“…At present, a variety of methods have been developed to detect miRNA let-7a, such as electrochemiluminescence, 7,8 fluorescence assays, 9 and electrochemical methods. 10,11 Compared to the other methods, the electrochemical biosensing technology has the advantages of simpleness, low cost, and high sensitivity, which are more conducive to the establishment of practical analytical devices.…”
Section: Introductionmentioning
confidence: 99%